Regional Prevalence of Short Stature in Saudi School-Age Children and Adolescents - Mohammad I. El Mouzan; Abdullah S. Al Herbish; Abdullah A. Al Salloum; Ahmad A. Al Omer; Mansour M. Qurachi (The Scientific World Journal)
Objective. To assess the magnitude of regional difference in prevalence of short stature in Saudi children and adolescents. Subjects and Methods. A representative sample from three different regions of the Kingdom of Saudi Arabia (KSA) (North, Southwest, and Center) was used to calculate the prevalence of short stature (standard deviation score less than -2) in children 5 to 17 years of age. Results. There were 9018 children and adolescents from 5 to 17 years of age (3366, 2825, and 2827 in the Northern, Southwestern and Central regions, resp.) and 51% were boys. In both school-age children and adolescents, there was a significantly higher prevalence of short stature in the Southwestern than in the Northern or the Central region (P < 0.0001). Conclusion. The finding of significant regional variation between regions helps in planning priorities for research and preventive measures.